Reviews Kuznetsov SL, Mushkambarov N.N. Gistologiya, tsitologiya i embriologiya [Histology, cytology and embryology]: textbook. Moscow: Meditsinskoye informatsionnoye agentstvo; 2016. 640 p. Russian. - journal "Morphologia", Editorial office of (Морфологія / Morphologia / Morfologìâ, 2017)
The textbook was written in accordance with the approved by the Ministry of Education of the Russian Federation in 2002 a program of the course of histology, cytology and embryology for medical universities.